Moving toward student-faculty partnership in systems-level assessment: A qualitative analysis - Curtis, Nicholas A; Anderson, Robin D. (International Journal for Students as Partners, 2021)
Partnership models have been effective across many areas of higher education such as involving students as teaching and learning consultants, in course design and redesign, and as co-instructors. However, there are few systems-level (i.e., entire programs or institutions) examples of partnership work and virtually none in systems-level assessment. Systems-level assessment models, such as program-level assessment in the United States, are used to inform broad changes to academic programs. Thus, student input may be crucial. This study sought to explore the broad factors that underlie potential student-faculty partnership efforts in systems-level assessment. Participants were faculty and staff members based in the United States and the United Kingdom who engaged in student-faculty partnerships at the program and/or classroom level. Qualitative coding and analyses of interviews with participants resulted in seven primary themes. This study examines patterns evident in student-faculty partnership work across several areas of higher education and begins to lay the foundation for a theory of student-faculty partnership in systems-level assessment.